Unit and fractional roots in the presence of abrupt changes with an application to the Brazilian inflation rate - Luis A. Gil-Ala\~na (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We analyse in this article the monthly structure of the Brazilian inflation rate by means of fractionally integrated techniques. This series is characterized by strong government interventions to bring inflation to a low level. We use a testing procedure due to Robinson (1994) which allow us to model the underlying dynamic of the series in terms of I(d) statistical models, while the government interventions are specified in terms of dummy variables. The results show that the series can be described in terms of an I(0.75) process with some of the interventions having little impact on the series.
urn:nbn:de:kobv:11-10050366
Keywords: C22; 330; Long memory; Fractional integration